Zelentsoviella jugorica gen. nov, sp. nov., a new Orthocladiinae from Russian Arctic (Diptera, Chironomidae) - Krasheninnikov, Andrey Borisovich (Zootaxa, 2019)
Zelentsoviella n. gen. is erected based on the male of Z. jugorica n. sp. from Yugorsky Peninsula in Russian Arctic. The genus can be separated from other Orthocladiinae genera on the basis of the combination of the following characters: bare eyes and wings; palp consists of 4 segments; wing with obtuse anal lobe; R4+5 ending distal to end of M3+4; squama with 2 setae; acrostichals 2 on mid-scutum; hind tibial comb is partially reduced and consists of 6 weak setae; pulvilli reduced; virga absent; the long part of the gonostylus is smoothly bent and gradually narrows to the apex, is covered with macrosetae and microsetae; crista dorsalis absent; the additional part of the gonostylus has the shape of a palm with a bent thumb. The K2P sequence divergence between Zelentsoviella jugorica gen. n., sp. n. and some Orthocladiinae was 0,068 – 0,229. Unidentified specimens from Canada (British Columbia) are nearest to Zelentsoviella gen. n.